Mammary-coronary anastomosis: technical aspects - Delgado, Fernando; Sanguinetti, Julio; Gastambide, Carmelo; Maglione, Hugo; Despagne, Paul; Ramírez, Wilson (Cirugía del Uruguay, 1973)
The past and present of miocardial revascularization is considered with special reference to the use of the aortic-coronary bridge with the safena vein. Relative and absolute Jimitations to the use of venous grafting are revised and the value of the mammary artery for grafting purposes discussed. The technical possibilities of mammary-coronary anastomosis are tried in animals and on dead bodies, arriving at the conclusion that it is possible to perform it utilizing the anterior descendent coronary and the proximal sectors of the right circumflex coronary. Optical magnification was not required for the operation. Special care should be taken in performing a neat suture.